Effectiveness of a Transtheoretical Model-Based Intervention to Improve Blood Pressure Control of Hypertensive Patients in China: A Clustered Randomized Controlled Trial - Chen, Ping; Shen, Ying; He, Chao; Sun, Xinying (Frontiers in Public Health, 2022)
Background: Hypertension can result in great cardiovascular risk while patients’ medication adherence and blood pressure control were suboptimal. Therefore, we conducted a 12-month clustered-randomized controlled trial to evaluate the effectiveness of Transtheoretical model-based (TTM) health intervention mode on newly-diagnosed Chinese hypertensive patients’ blood pressure. Methods: This trial was conducted in six primary health care centers, Shunyi District, Beijing, China from Sep, 2016 to Sep, 2017. A total of 400 patients were included and randomized, 194 in the control group and 206 in the intervention group. Patients in the intervention group received TTM-based health intervention and those in the control group received usual care. Multilevel modeling was used to adjust for clustering effect and repeated measurements. Results: Patient’s systolic blood pressure was reduced by 4.534 mmHg at 3-month follow-up (95% CI [-3.054, -1.403], P =0.005), 3.982 mmHg at 6-month follow-up (95% CI [-7.387, -0.577], P =0.022), and 5.803 mmHg at 12-month follow-up (95% [-9.716, -1.891], P =0.004). Patient’s diastolic blood pressure was reduced by 3.383 mmHg at 3-month follow-up (95% CI [-5.724, -1.042], P =0.005), 0.330mmHg at 6-month follow-up (95% CI [-2.870, 2.210], P =0.799) and 3.129 mmHg at 12-month follow-up (95% CI [-6.048, -0.21], P =0.036). Patients’ medication adherence was improved at all three time points. For stages of change for taking medication, patients in the intervention group were 8.401-fold more likely to be in a higher stage at 3-month follow-up (95% CI [4.186, 16.862], P < 0.001). The odds ratio of being in a higher stage was 8.454 at 6-month follow-up (95% CI [3.943, 18.123], P < 0.001) and 19.263 at 12-month follow-up (95% CI [7.979, 46.505], P < 0.001) Conclusion: Transtheoretical model-based health intervention might be a promising strategy to improve newly-diagnosed hypertensive patients’ medication adherence in community.